PROPOSED CONTENT MARKETING STRATEGY FOR KALÃA SPACE TO INCREASE ONLINE PRESENCE - Made Arini Candraputri, Luh
The rise of local brands in Indonesia, especially since the COVID-19 pandemic, caused intense competition among themselves. Kalëa Space sees the need for a collective space that could help those local brands support and lift each other instead of competing against each other.